The Geography of Tourism in Ghana - Asiedu, A.B. (My University, 2013)
Tourism, which is increasingly viewed as an attractive development option for many parts of the developing world, has been studied by an increasing number of academic disciplines even though no widely accepted interdisciplinary field of tourism studies has yet been defined. While recognising the contributions of other disciplines to the subject matter of tourism however, geographers have been found to make distinct and significant contributions. Travelling from one’s place of normal residence to a distant location where tourism experience transpires involves spatial interaction which is a major and pivotal theme in geographical studies. Inspite of the growing recognition and importance of geography in tourism studies, not much attention has been given to it even in the wider fields of academic geography. It is against this background and the limited local materials on the topic that have necessitated the need for this chapter on the Geography of Tourism in Ghana. The chapter is organized under five (5) sections. The first section is the introduction section and this is followed in section two with a discussion on the concept of tourism. The third section deals with the subject matter of tourism whiles the fourth section is devoted to a discussion on geography of tourism in Ghana. The final section is on study conclusions and an agenda for future studies on geography of tourism in Ghana.